Anatomical and ultrastructural aspects of root and mycorrhiza of Anadenanthera peregrina (L.) Speg. var. falcata (Benth.) Altschul (Leguminosae-Mimosoideae) - Gross,Eduardo (2003)
A. peregrina var. falcata form mutualistic symbiosis with arbuscular mycorrhizal fungus. An anatomical and ultrastructural study was carried out to analyze some aspects of this simbiotic association as well as some root features. The results evidenced the presence of fibers with non-lignified thicked secondary walls in the stele and sparse papillae on root surface. A. peregrina var. falcata mycorrhizas presented features of Arum-type (intercellular hyphae) and Paris-type (extensive coils) arbuscular mycorrhiza. Their general appearance with extraradical hyphae, intracellular coils, intercellular hyphae and arbuscules, is in agreement with arbuscular mycorrhizas of several plants. The ultrastructural observations showed that in intercellular hyphae and arbuscules vacuoles were dominant and that in rough endoplasmatic reticulum and small vesicles seems to be associated with arbuscule senescence process.